Pharmaceutical Profile and Importance of Ashtasamskaras of Parada in Rasashastra - Shraddha N Dhundi, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmaceutical Profile and Importance of Ashtasamskaras of Parada in Rasashastra